The Adventures of Isabel - Nash, Ogden, 1902-1971.; Marshall, James, 1942- (Boston : Joy Street Books, 1991)
The feisty Isabel defeats giants, witches, and other threatening creatures with ease
NP
Keywords: American poetry; Heroines in literature -- Poetry; Women heroes -- Poetry